Boundedness of θ-Type Calderón–Zygmund Operators and Commutators in the Generalized Weighted Morrey Spaces - Hua Wang (Journal of Function Spaces)
We first introduce some new Morrey type spaces containing generalized Morrey space and weighted Morrey space as special cases. Then, we discuss the strong-type and weak-type estimates for a class of Calderón–Zygmund type operators Tθ in these new Morrey type spaces. Furthermore, the strong-type estimate and endpoint estimate of commutators [b,Tθ] formed by b and Tθ are established. Also, we study related problems about two-weight, weak-type inequalities for Tθ and [b,Tθ] in the Morrey type spaces and give partial results.